Kontribusi Ushul Fiqh dalam Kajian Kritik Matn Hadith - Idris Masudi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2016)
This paper describes the theories of ushul fiqh as an approached in the study of hadith criticism matn and try to answer the question to what extent ushul accommodated by science musthalah al- Hadith . The findings from this study is that the theories of usul fiqh as Jam' al - riwayah , nasikh - mansukh , tarjih, and maqasid al - Sharia are important theories used by the experts of hadith, although in practice, sometimes there are different results among scholars of usul fiqh and hadith scholars in addressing honor a tradition that was born contradictory.